2020
DOI: 10.1007/s00028-020-00558-1
|View full text |Cite
|
Sign up to set email alerts
|

On the global well-posedness of focusing energy-critical inhomogeneous NLS

Abstract: We consider the focusing energy-critical inhomogeneous nonlinear Schrödinger equation:3 , and p = 5 − 2b. On the road map of Kenig-Merle [22] we show the global well-posedness and scattering of radial solutions under energy condition, and rigidity condition −bg(x) ≤ x · ∇g(x). We also provide sharp finite time blowup results for non-radial and radial solutions. For this we utilize the localized virial identity.2010 Mathematics Subject Classification. M35Q55, 35Q40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…We say that (1.1) is locally well-posed if there exists a maximal existence time interval I * such that there exists a unique solution u ∈ C(I * ; Ḣ1 ) and u depends continuously on the initial data. The local well-posedness (LWP) can be usually shown by a contraction argument based on the Strichartz estimates [4,8,6,15]. In this paper the L q0 t L r0 x (|x| −r0 γ * )-norm controls our whole contraction argument.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We say that (1.1) is locally well-posed if there exists a maximal existence time interval I * such that there exists a unique solution u ∈ C(I * ; Ḣ1 ) and u depends continuously on the initial data. The local well-posedness (LWP) can be usually shown by a contraction argument based on the Strichartz estimates [4,8,6,15]. In this paper the L q0 t L r0 x (|x| −r0 γ * )-norm controls our whole contraction argument.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to establish a global theory for radial solutions: the global well-posedness (GWP), the scattering, and the finite time blowup to (1.1). In the previous papers [8,6] the authors considered a global theory for g with 0 ≤ b < 4 3 which was shown by a concrete concentration-compactness argument based on the local theory and profile decomposition. The restriction of index b is due to the lack of local theory of (1.1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy-critical case s = 1 was also handled by the authors [19] for 0 < α < min{n/2, 2} and n ≥ 3. By this weighted norm approach, some related results in [7] for the focusing energy-critical case could be also improved in [9]. The gap 1/3 ≤ s < 1 was recently filled in [1] by utilizing the known Strichartz estimates [16] in Lorentz spaces L p,2 .…”
Section: Introductionmentioning
confidence: 99%